Monitoring of degradation of photovoltaic panels using infrared method - Pavel Šimon; Marcela Koščová; Miroslav Ďulík; Zdeněk Dostál (Acta Montanistica Slovaca, 2010)
Monitoring of solar panels is important in order to ensure optimal performance of solar panels. Their properties are subjectto change due to aging, weather effects and exposure to environment. Infrared camera provides monitoring of degradation of solarpanels. Similarly, thermal camera can detect errors in panels, which occured during production or assembly.